I, too, am America - Hughes, Langston, 1902-1967.; Collier, Bryan (New York : Simon & Schuster Books for Young Readers, 2012)
Presents the popular poem by one of the central figures in the Harlem Renaissance, highlighting the courage and dignity of the African American Pullman porters in the early twentieth century.
"Reprinted from: The collected poems of Langston Hughes. Copyright 1994 by The Estate of Langston Hughes"--Copyright p.
Keywords: African Americans -- Juvenile poetry; Children's poetry, American; African Americans -- Poetry; American poetry; African Americans -- Poetry; Picture Book